Magneto-responsive hyaluronan hydrogel for hyperthermia and bioprinting: Magnetic, rheological properties and biocompatibility - Vítková, L; Kazantseva, N; Musilová, L; Smolka, P; Valášková, K; Kocourková, K; Humeník, M; Minařík, A; Humpolíček, P; Mráček, A; Smolková, I (APL bioengineering, 2023)
Magneto-responsive soft hydrogels are used for a number of biomedical applications, e.g., magnetic hyperthermia, drug delivery, tissue engineering, and neuromodulation. In this work, this type of hydrogel has been fabricated from hyaluronan (HA) filled with a binary system of Al2O3 nanoparticles and multicore magnetic particles (MCPs), which were obtained by clustering of superparamagnetic iron oxide FeOx NPs. It was established that the presence of diamagnetic Al2O3 has several positive effects: it enhances the hydrogel storage modulus and long-term stability in the cell cultivation medium; prevents the magnetic interaction among the MCPs. The HA hydrogel provides rapid heating of 0.3 °C per min under exposure to low amplitude radio frequency alternating magnetic field. Furthermore, the magneto-responsive hydrogel was successfully used to encapsulate cells and extrusion-based 3D printing with 87±6% cell viability, thus providing a bio-ink. The combination of high heating efficiency, softness, cytocompatibility, and 3D printability of magnetic HA hydrogel leads to a material suitable for biomedical applications.